Dynamics of gut microbiota during a cycling Grand Tour is related to exercise performance and modulated by dietary intake - Fernández, M.; Fernández, J.; Martínez, P.; Rodríguez-Alonso, M.; Ortolano, R.; Pinto, P.; Castilla, J.; Coto, A.; Ruiz, L.; Villar, C. J.; Tomás, C.; Margolles, A.; et al. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Regular exercise has been described as a factor modifying both the diversity and the relative abundance of certain bacterial phyla or families, although the few studies that have been carried out on this show important methodological differences and divergent results. To our knowledge, the effect of a cycling stage race on the gut microbiota composition and metabolic activity of professional cyclists has not been analysed. Studying the composition of the intestinal microbiota in this context can help both to understand its potential modulatory role in the response to exercise and to optimize and personalize the use of supplements. The aim of this cohort study was to analyse the dynamics of faecal microbiota composition of professional cyclists over a Grand Tour, and their relationship with performance and dietary intake.